WHAT IS BIBLICAL MEDIA CRITICISM? A MEDIACRITICAL READING OF LUKE 9:51-56 - Loubser, Johannes Albertus (Scriptura, 2002)
In Luke 9:51-56 Jesus rebukes his disciples for wishing revenge on the Samaritans for their lack of hospitality. The paper investigates the rich residual orality in the text and the probable transformations that occurred when this narrative was recorded and translated. A review of the available communications technology at the time of text production is followed by an examination of explicit and implicit data on orality and literacy. Some exciting communicative and social aspects of the text are explored. The paper concludes with a brief reflection on the relation between transmediation and the ethics of interpretation.